2009
DOI: 10.1007/s10495-009-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate thymoquinone-induced apoptosis and activate ERK and JNK signaling

Abstract: Thymoquinone (TQ), a component of black seed essential oil, is known to induce apoptotic cell death and oxidative stress, however, the direct involvement of oxidants in TQ-induced cell death has not been established yet. Here, we show that TQ inhibited the proliferation of a panel of human colon cancer cells (Caco-2, HCT-116, LoVo, DLD-1 and HT-29), without exhibiting cytotoxicity to normal human intestinal FHs74Int cells. Further investigation in DLD-1 revealed that apoptotic cell death is the mechanism for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
181
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(200 citation statements)
references
References 46 publications
17
181
1
1
Order By: Relevance
“…The active principles in NSO have been found to exert antineoplastic effects both in vitro and in vivo using various models of carcinogenesis. The active principles of N sativa showed cytotoxicity against number of cancer cells, such as Ehrlich ascites carcinoma, Dalton's lymphoma ascites and Sarcoma-180 cells in a concentration dependent manner (Salomi et al, 1992;El-Najjar et al, 2010). We found that the NSO extracts, even at lower concentrations exhibit the inhibition of A-549 cells, and the cytotoxicity was found more than the NSE extract.…”
Section: Discussionmentioning
confidence: 73%
“…The active principles in NSO have been found to exert antineoplastic effects both in vitro and in vivo using various models of carcinogenesis. The active principles of N sativa showed cytotoxicity against number of cancer cells, such as Ehrlich ascites carcinoma, Dalton's lymphoma ascites and Sarcoma-180 cells in a concentration dependent manner (Salomi et al, 1992;El-Najjar et al, 2010). We found that the NSO extracts, even at lower concentrations exhibit the inhibition of A-549 cells, and the cytotoxicity was found more than the NSE extract.…”
Section: Discussionmentioning
confidence: 73%
“…The p-quinones DOX and TQ can act either as anti-oxidants or pro-oxidants depending on the given redox environment. The anti-proliferative and apoptotic effects of TQ in human colon cancer cells but not in normal intestinal cells were shown by El-Najjar et al to be induced via the generation of ROS [27]. Similary, different apoptosis-triggering mechanisms in normal and tumour cells were established for DOX [23].…”
Section: Mitochondrial Membrane Potential and Generation Of Rosmentioning
confidence: 89%
“…The over expression of CARD16 was validated with RT-qPCR method which was 9.02 up-fold change in breast cancer cell but showed only 1.64 up-fold in colon cancer (Table 5). Previous study on different type of colon cancer reported that Thymoquinone 40 µM concentration cannot lead the cell significantly in the apoptosis process after 24 hours especially in HT-29 cell line [11]. The expression of MTR gene in breast cancer was found to be up-regulated in microarray result by 3.91.…”
Section: Discussionmentioning
confidence: 83%